Enhancing corporate social responsibility through microblog platform: a consumer behavior information analysis approach - Mohd Hassan, Nurul'ain; Xiangzhou, Hua; De Costa, Feroz (World Textile Information Network, 2024)
Understanding how users behave significantly impacts their purchasing decisions, making the study of corporate social responsibility's influence on consumer behavior a recent focal point in the information field. However, challenges arise during the analysis of user behavior information, such as decision-making rationality and the limited availability of behavioral data.To address these issues, this paper presents a method for analyzing consumer behavior information based on the microblog platform. This approach aims to track both consumer user behavior and purchase decisions. Initially, the microblogging platform is utilized to gather information on corporate social responsibility from consumers. Subsequently, consumer user behavior data is summarized through the microblog platform, and purchase decisions are categorized based on this behavioral information.The next step involves transmitting purchase decision information through the microblogging platform, aligning with social responsibility standards. This process encourages the integration of behavioral information and purchase decisions across microblogging platforms. The outcomes of the analysis indicate that, supported by social responsibility standards, the microblog platform can collect more comprehensive behavioral data, enhancing the rationality of consumer purchase decisions. Additionally, the microblogging platform plays a role in promoting corporate social responsibility, aligning with the requirements of informed purchase decisions.